Note on the Doxographic Tradition of the Terms 'Philosopher' and 'Philosophy' - Camino Macedo, Federico (1999)
This note is a presentation, without pretending completion, of the doxographic tradition of the terms "philosopher" and "philosophy, "showing their variation in meaning. lt deals with the attribution to Pythagoras of these terms'creation, starting with Plato's and Aristotle's decisive relevance in the establishment and configuration of doxography.